2008
DOI: 10.2319/0003-3219(2008)078[0682:ioaair]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Attachments and Interproximal Reduction on the Accuracy of Canine Rotation with Invisalign

Abstract: Objective: To evaluate the influence of attachments and interproximal reduction on canines undergoing rotational movement with Invisalign. Materials and Methods: In this prospective clinical study, 53 canines (33 maxillary and 20 mandibular) were measured from the virtual TREAT models of 31 participants treated with anterior Invisalign. The pretreatment virtual model of the predicted final tooth position was superimposed on the posttreatment virtual model using ToothMeasure, Invisalign's proprietary measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 7 publications
4
100
0
12
Order By: Relevance
“…Eleven relevant publications were identified: four studies 5,10-12 were retrospective non-randomized, five studies 4,[13][14][15][16] were prospective non-randomized, and two studies 17,18 were prospective randomized. The article selection process is illustrated in the PRISMA Flow Diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven relevant publications were identified: four studies 5,10-12 were retrospective non-randomized, five studies 4,[13][14][15][16] were prospective non-randomized, and two studies 17,18 were prospective randomized. The article selection process is illustrated in the PRISMA Flow Diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, teeth with rounded crowns seem to be more difficult to rotate with CAT. Furthermore, in 2008 Kravitz et al 13 stated that IPR influenced in a positive way the correction of rotations, while in 2005 Djeu et al 10 supported the use of attachments to improve the accuracy of this movement. In their retrospective study, Simon et al, 12 analyzing premolar rotations of .10u, concluded that the use of attachments and the amount of movement per aligner had a great impact on the treatment predictability; reducing the staging and using attachments increase the predictability of tooth movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attachments are generally placed on the teeth to increase the undercuts and retention of the appliance to facilitate the desired tooth movement [18]. However, the current attachments are considered to be only partially effective [32], [33]. An improved system utilizing small magnetic attachments has been put forward to enhance the capabilities of this appliance.…”
Section: Application Of Magnetic Forces For Tooth Movement In Combinamentioning
confidence: 99%